FRI0494 Steroid-Sparing Effect of Anakinra (Kineret®) in the Treatment of Patients with Severe Cryopyrin-Associated Periodic Syndromes. (9th June 2015) - Kullenberg, T.; Hallén, B.; Olivecrona, H.; Leinonen, M.
Abstract : Background: Cryopyrin-Associated Periodic Syndromes (CAPS) include a group of rare inherited autoinflammatory diseases consisting of Familial Cold Autoinflammatory Syndrome (FCAS), Muckle-Wells Syndrome and the most severe form, Neonatal-Onset Multisystem Inflammatory Disease (NOMID). One goal of anakinra therapy is to reduce the concomitant use of steroids. Side effects involving the cardiovascular system and infections are the most frequently reported adverse events (AEs) in steroid-treated patients with rheumatic diseases 1 . An analysis of a previous data cut of this study indicated a substantial decrease in the mean daily prednisone-equivalent dose in 16 patients with severe CAPS treated with anakinra for up to 60 months 2 . Objectives: The objective of the present analysis is to further evaluate the steroid-sparing potential and its consequences in an expanded cohort of patients with severe CAPS treated with anakinra. Methods: A prospective, open-label, single arm study of anakinra including 43 patients was conducted at the National Institutes of Health 3 . The primary efficacy endpoint, Diary Symptom Sum Score (DSSS), collected daily up to 60 months, included 5 symptoms (fever, rash, joint pain, vomiting, headache), each scored from 0 (no symptoms) to 4 (severe symptoms). Use of steroid medication was obtained from the patient diary. The prednisone dose was to be decreased by 20% at each study visit in which the subject's disease activity was "moderately" or "significantly" improved. Different types of steroids were converted into prednisone-equivalent doses to enable comparisons. The AEs were analyzed with the infection rate (number of infections per patient years of treatment). Results: The proportion of steroid-treated patients in the ITT population decreased from 47.1% at baseline to 33.3% at Month 60. Among the patients using steroids at baseline the mean (SEM) prednisone-equivalent dose was 0.76 (0.31) mg/kg at baseline, but doses were promptly tapered during the first 6 months to 0.15 (0.03) mg/kg. At Month 36 and Month 60 there was a further decline in the prednisone-equivalent dose to 0.08 (0.02) and 0.05 (0.02) mg/kg, respectively. DSSS decreased rapidly both in patients not using steroids and in patients reducing the steroid dose. The decrease was maintained up to Month 60 (p<0.001 in both subgroups at each follow-up visit). Among patients reducing the steroid dose, the infection rate was reduced from 3.4 events/patient year (Year 1) to 1.4 (Year 5). Conclusions: The steroid dose among patients using steroids at baseline decreased from 0.76 mg/kg/day to 0.05 mg/kg/day after 60 months of anakinra treatment and the positive anakinra treatment effect was independent of reduced steroid use. The infection rate decreased in patients who reduced or stopped steroid use during the study. Overall, it can be concluded that steroids could be tapered and in some cases stopped without affecting the positive effect of anakinra treatment and that the reduced steroid use coincided with a decreased risk for infections. References: Hoes et al. Ann Rheum Dis. 2007;66:1560-67. Sibley et al. Arthritis Rheum. 2012;64:2375-86. Goldbach-Mansky et al. NEJM. 2006;355:581-92. Acknowledgements: The authors would like to thank Dr. Goldbach-Mansky and the NIH team. Disclosure of Interest: T. Kullenberg Employee of: Sobi, B. Hallén Shareholder of: Sobi, H. Olivecrona Employee of: Sobi, M. Leinonen Consultant for: Sobi